ANALISIS PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR KARYAWAN BPJS KETENAGAKERJAAN DENGAN AFFECTIVE COMMITMENT SEBAGAI VARIABEL MEDIASI - Einstain Klein Marthing; Christine Winstinindah Sandroto (Prosiding Working Papers Series In Management, 2018)
This study aims to prove the effect of Perceived Organizational Support (POS) on Organizational Citizenship Behavior (OCB) mediated by the Affective Commitment (AC). This research was conducted at the Social Employment Insurance Administration Organization Headquarters by involving certain divisions or deputies in the company. A total of 125 questionnaires were distributed and 60 questionnaires were returned and could be processed, so the sample of this study was 60 respondents and processed using SPSS v22 software and Hayes PROCESS v3 macro.The results of this study indicate that there is a positive and significant effect between POS on OCB, POS also shows a positive and significant effect on AC. AC has a positive and significant effect on OCB and OCB mediates the effect of POS on OCB on employees of the Social Employment Insurance Administration Organization Headquarters.Keywords: Perceived Organizational Support (POS), Affective Commitment, Organizational Citizenship Behavior.